Analisis Prinsip dan Prosedur Penilaian di Kelas V SDN 136 Pekanbaru - Arifah; Anggi Yusiana Sari; Assyuqia Balqis; Phutiatti Lindra Fahlevy; Hendri Marhadi (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This research is motivated by the importance of implementing assessment principles and procedures in schools. The principles and procedures of learning assessment are part of the educational process which aims to measure students' understanding, achievement and progress in the teaching-learning process. The purpose of this study was to analyze the principles and procedures of correct assessment in grade V at SDN 136 Pekanbaru. This research uses qualitative methods with interview techniques and direct observation. The results of this study indicate that the principles and procedures of assessment in grade V have been carried out by applying the principles of validity, objectivity, fairness, integration, openness, thoroughness and continuity, systematic, criteria-based, and accountability and the assessment procedures applied consist of assessment planning, assessment implementation, and assessment evaluation.